Studi Eksperimental Kemampuan Biosementasi Bakteri Bacillus Subtilis Menggunakan Material Pozzolan Fly Ash untuk Pemadatan Tanah pada Tanah Lunak di Kecamatan Wonoayu-Sidoarjo - Rafendi wahyutama; Laily Endah Fatmawati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Clay soils with high plasticity often pose challenges in construction due to their tendency to swell when wet and shrink when dry, resulting in low bearing capacity. This study investigates the effectiveness of soil stabilization using Bacillus subtilis bio-cementation combined with pozzolanic fly ash on soft clay in Wonoayu, Sidoarjo. Soil samples were collected at depths of 100–150 cm and prepared with varying proportions of fly ash (10%, 20%, and 30%) and bacterial suspension (3%). The stabilization performance was evaluated through the Proctor test to determine optimum moisture content (OMC) and maximum dry density (MDD). Results indicate that the addition of fly ash and Bacillus subtilis significantly reduced OMC while increasing MDD compared to natural soil. The most effective mixture was 30% fly ash and 3% Bacillus subtilis, yielding an OMC of 19% and MDD of 2.443 gr/cm³. These findings suggest that the combination of fly ash and Bacillus subtilis offers an efficient and environmentally friendly method for improving the compaction and mechanical properties of expansive clay soils.